The role of joint auditing in reducing income smoothing methods - a field study on a sample of external audit offices in the state of Khartoum - Mubarak Hussein Moussa, Asaad (Journal of Research in Finance and Accounting, 2026)
The study aimed at identifying the concept, objective and types of joint audit in addition to identifying the concept and objective of earning management practices. Furthermore Study the role of joint audit in reducing earning management Practices in revenues and expenses. The study found that conducting joint audit leads to mitigate earning management practices in revenues and expenses, thus increase the reliance of financial reports.